Effects of intravenous arginine on the healing of human skin graft donor sites: A randomized controlled trial - Li, Ke; Lin, Wei; Wu, Li-Jun; Qi, Qiang; Shen, Guo Liang; Liu, Jian Jiang; Chen, Wei Xin; Xu, Jun; Qian, Hangen; Zhao, Xiao Yu (Bangladesh Journal of Pharmacology, 2015)
We expounded the effect of intravenous arginine on the healing of human skin graft donor sites. This randomized study was double blind and controlled by placebos from October 2012 to May 2015. Nine patients were selected into the arginine group and 10 were selected into the control group. There was no significance in age, weight, BMI, CRP, albumin and total plasma protein in arginine and control groups. Angiogenesis, re-epithelialization and neutrophil influx of wound healing were measured. The concentrations of plasma amino acid were measured to evaluate our intervention. In our study, plasma arginine and ornithine concentrations in arginine group were the highest after arginine-treated at 2 days. Supplementation of intravenous arginine could not affect on healing of human skin graft donor sites, improve angiogenesis, reepithelialization or neutrophil influx in rats.